2016
DOI: 10.1002/mrd.22670
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of different stages of pigeon ovaries by RNA‐sequencing

Abstract: The pigeon ovary is an ideal model for deciphering the molecular mechanism of folliculogenesis. While most analysis has focused on the influence of hormones and factors on ovarian follicle development in this model, changes occurring in the ovarian stroma can also be extremely informative. Here, we profiled the transcriptome of pigeon ovaries at pre-ovulation, post-ovulation, and 5-6 days after ovulation using RNA-sequencing to gain insights into the molecular and cellular events mediating ovary activity. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Considering the characteristics of hen laying, the regressing tract model is usually obtained by controlling the hen's diet (Jeong et al, 2013; J. Y. Yu & Marquardt, 1973); however, pigeons have a two‐egg clutch and only need approximately 10–20 days before the next reproduction cycle (Xu et al, 2016). In the clutch, rather than being caused by man‐made interferences, the reproductive tract naturally undergoes a reproductive cycle consisting of developing, developed, and regressing stages.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristics of hen laying, the regressing tract model is usually obtained by controlling the hen's diet (Jeong et al, 2013; J. Y. Yu & Marquardt, 1973); however, pigeons have a two‐egg clutch and only need approximately 10–20 days before the next reproduction cycle (Xu et al, 2016). In the clutch, rather than being caused by man‐made interferences, the reproductive tract naturally undergoes a reproductive cycle consisting of developing, developed, and regressing stages.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to mammalian models, similar studies are limited in non-mammalian species. In the pigeon, pre-ovulatory and post-ovulatory ovaries were analyzed for transcriptomes, and more than 400 DEGs were identified ( 52 ). In teleosts, a few studies on ovarian transcriptomes have been reported using subtractive hybridization, serial analysis of gene expression (SAGE), microarray, or RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, transcriptomic data are compared between embryos or organs during their development in different species (Pantalacci and Sémon 2015), including birds (Chen et al 2016;Xu et al 2016). By comparing the transcriptome between pigeon ovaries pre-and post-ovulation, Xu et al (2016) investigated what changes occurred in the gene expression profiles during different stages of ovulation. The authors found that immune genes were enriched in the transcriptome of the post-ovulation stroma.…”
Section: Evolutionary Developmental Biologymentioning
confidence: 99%
“…The authors found that immune genes were enriched in the transcriptome of the post-ovulation stroma. This suggests that the immune response is at least partly responsible for post-ovulatory follicle regression and elimination (Xu et al 2016).…”
Section: Evolutionary Developmental Biologymentioning
confidence: 99%